Financial Performance Analysis Based on Profitability Ratio (Study at PT Astra International Tbk Period 2009-2018) - Ali, Muhammad; Dianita, Mirna; Hadian, Niki; Lisa Aryanti, Maya; Dewi Wahyuningsih, Nila (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to determine the description of the level of profitability at PT Astra International Tbk. The data used in this study are secondary data in the form of the annual financial statements of PT Astra International Tbk for the period 2009-2018. The method used in this research is the descriptive method. The average value of Gross Profit Margin (GPM) for the period 2009-2018 was 20.1%; the lowest value of GPM was 18% in 2013, and the highest value of GPM was 23% in 2009. Average Net Profit Margin (NPM) of 11.4%, the lowest value of NPM of 8% in 2015, and the highest value of NPM of 13%. The average value of return on assets (ROA) is 10.3%; the lowest value of ROA was 6% in 2015, and the highest value of ROA was 15% in 2010. The average value of return on equity (ROE) is 20.2%, the lowest value of ROE is 12%, and the highest value of ROE is 29%.